Outcome of Levator Resection in Congenital Ptosis with Poor Levator Function - Abid Latif, Ejaz Latif, Rao Muhammad Rashad Qamar, Muhammad Younis Tahir (Pakistan Journal of Ophthalmology, 2011)
Purpose: Purpose of the study is to evaluate the success of levator resection in congenital ptosis with poor levator function. Material and Methods: It was a single center, prospective, interventional case series. The study was carried out at Department of Ophthalmology, Bahawal Victoria Hospital, Bahawalpur from March 2008 to November 2010. We selected 50 cases from outdoor department by universal sampling technique. Levator resection was carried out in all 56 cases (eyes) of congenital Ptosis (with 06 bilateral cases) with poor levator function (less than 4mm) after taking informed written consent. Patients were subjected to general anesthesia. Data was collected on special proforma and was analyzed with the help of SPSS. Results: The study population comprised of 56 eyes of 50 cases of congenital ptosis. Male to female ratio was 3:1. Two bilateral cases were females and four were males. Age ranged between 04-32 years (Mean = 14 years). About 75% patients were between 13 and 24 years. The results were excellent in majority (67.8%) with complete lid closure. Good results were seen in 17.85% with only 7.14% with fair and poor outcome each. The major cosmetic defect in all cases was lid lag on extreme downward gaze. The operation is extremely laborious but fully justified by the good results. Conclusion: Levator resection in congenital Ptosis with poor levator function is a viable option for cosmesis especially in unilateral cases.